Is population structure in the European white stork determined by flyway permeability rather than translocation history?. Issue 15 (7th November 2013) - Shephard, Jill M.; Ogden, Rob; Tryjanowski, Piotr; Olsson, Ola; Galbusera, Peter
Abstract: European white stork are long considered to diverge to eastern and western migration pools as a result of independent overwintering flyways. In relatively recent times, the western and northern distribution has been subject to dramatic population declines and country‐specific extirpations. A number of independent reintroduction programs were started in the mid 1950s to bring storks back to historical ranges. Founder individuals were sourced opportunistically from the Eastern and Western European distributions and Algeria, leading to significant artificial mixing between eastern and western flyways. Here we use mitochondrial and microsatellite DNA to test the contention that prior to translocation, eastern and western flyways were genetically distinct. The data show a surprising lack of structure at any spatial or temporal scale suggesting that even though birds were moved between flyways, there is evidence of natural mixing prior to the onset of translocation activities. Overall a high retention of genetic diversity, high N ef, and an apparent absence of recent genetic bottleneck associated with early 20th century declines suggest that the species is well equipped to respond to future environmental pressures. Abstract : European white stork have long been considered to have genetically distinct migration flyways. This study addresses this contention with specific attention to natural levels of admixture and the impact of human‐mediated translocation programs.